Biodegradation of Pendimethalin by Three strains of Bacteria Isolated from Pesticide-Polluted Soils (University of Khartoum Journal of Agricultural Sciences, 2023)
Biodegradation of pendimethalin by three strains of bacteriaviz; Pseudomonas aeruginosa, Bacillus mycoides and Bacillus cereusisolated from pesticides polluted soil was studied in mineral salt medium.Pendimethalin was incubated with each of the three strains of bacteria andsamples were drawn at 0, 3, 7, 15 and 30 days for gas chromatographicanalysis. The loss in the initial concentration (400 ppm) over time wasmonitored and used to compute the half lives following a biphasic model.GC-MS was used to identify the major metabolites as well as to re-confirm the identity of the starting material (pendimethalin). The resultsshowed that the remaining amounts of pendimethalin recovered frommedia inoculated with Pseudomonas aeruginosa for 3, 7, 15 and 30 dayswere; 75.5%, 69.25%, 29.75 % and 19.25% respectively, While theamounts recovered from media inoculated with Bacillus mycoides were;48.75%, 46.25%, 39.25 % and 28.25% following the same order. On theother hand, the respective amounts recovered from media inoculated withBacillus cereus were; 45 %, 32.5 %, 30.5 % and 19.75% at 3, 7, 15 and30 days, respectively. Despite the significant drop in the starting material,no metabolites were detected in Bacillus cultures while only N-(1-ethylpropyl)-3-methyl-2, 6-diaminobenzine was detected in P. aeruginosaculture indicating the capability of these microorganisms of completemineralization of pendimethalin. Pendimethalin biodegradation by thethree types of bacteria followed a biphasic model with faster rate of
Keywords: Bacteria; pendimethalin; biodegradation; Sudan